Heating Treatment of Incoming Air Combustion Chamber on the E20 Fuel Mixture: Perlakuan panas udara masuk ruang bakar pada campuran bahan bakar E20 - Akbar Anugrah Ikhsani; Nurkoyim Kustanto; Boy Arief Fachri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This research was conducted to improve engine performance with a mixture of ethanol and gasoline, because the mixture of ethanol and gasoline fuel causes the value of the flash point and evaporation of fuel heat to be higher. To overcome this, the air entering the combustion chamber is carried out by being heated to 26°C (standard), 30°C, 40°C and 50°C, the fuel used is the E20 with engine revolutions of 2000 to 8000 revolutions per minute. The results showed that the highest torque of E20 fuel at 30°C with a value of 9.004 Nm increased by 0.27%. At the highest power, it is located at 30°C with a power of 5.99 kW 0.5%. For the lowest consumption in the 2000 round, it was found in the 30°C temperature treatment with a value of 1.4 Kg / Hp.Hour and for exhaust gas emissions the lowest hydro carbon value was found in the 30°C temperature treatment while the lowest value of carbon monoxide was found at the 50°C temperature treatment. These results show that the air heating treatment can improve engine performance.